Does dead wood availability drive abundance and biomass of wood-feeding termites in Caatinga dry forests? - Israel S. Silva; Alexandre Vasconcellos (International Journal of Tropical Insect Science, 2026)
Wood-feeding termites rely almost entirely on dead plant material as both habitat and food resource; therefore, their biomass and abundance are expected to reflect the availability of these detrital resources. This study investigated whether dead wood availability influences the abundance and biomass of wood-feeding termites in Caatinga dry forests. Sampling was conducted in seven areas, where standardized 10 × 10 m plots were established to quantify dead wood biomass and collect termites associated with woody substrates. Termites were counted and dried to determine dry biomass per unit area (m²). The relationship between dead wood biomass and termite abundance and biomass was evaluated using linear regression models and remained significant when accounting for the hierarchical sampling design. Dead wood biomass varied markedly among sites, ranging from 57.2 to 284.8 g·m⁻² (mean ± standard error: 218.3 ± 34 g·m⁻²). Termite abundance averaged 76.1 ± 14.5 ind·m⁻², while mean termite biomass was 0.0276 ± 0.0054 g·m⁻². A significant positive relationship was observed between dead wood biomass and termite abundance (R² = 0.77, p < 0.01), and also between dead wood biomass and termite biomass (R² = 0.62, p < 0.05). Our results emphasize that reductions in dead wood biomass, commonly associated with vegetation removal, directly affect termite abundance and, to a lesser extent, termite biomass, with potential implications for carbon and nutrient stocks and fluxes in seasonal dry forests.

Above- and below-ground termite biomass and abundance in the Caatinga dry forest region - Israel S. Silva; Alexandre Vasconcellos (Pedobiologia, 2026)

Influence of the urban matrix on termite genetic diversity and functional connectivity among Atlantic forest fragments - Rozzanna Esther Cavalcanti Reis de Figueirêdo Chaves; Gabriel de Sá Andrade; Wellington Santos Fava; Alane Ayana Vieira de Oliveira Couto; Israel S. Silva; Ricardo Koroiva; Alexandre Vasconcellos (Journal of Insect Conservation, 2026)
The change in land use caused by anthropogenic processes is probably the main driver of biodiversity loss across terrestrial ecosystems. In Brazil, the Atlantic Forest is currently distributed in small remnant patches, mostly in small and isolated forest fragments that harbor a disproportionately high share of global biodiversity. Urbanization causes biodiversity loss worldwide, but there is a lack of knowledge regarding its effects on the genetic diversity of tropical rainforest organisms. We aimed to evaluate whether the urban matrix of João Pessoa is permeable and, if so, to assess its influence on gene flow and genetic diversity between and within termite populations from different feeding groups sampled in four Atlantic Forest fragments. We used four nuclear DNA microsatellite markers. From 36 colonies, we sampled four individuals ( N = 144) among three termite species: Anoplotermes banksi (soil-feeder), Embiratermes neotenicus (wood–soil interface feeder), and Nasutitermes corniger (wood-feeder). Our study indicated maintenance of gene flow among forest remnants, which was unrestricted for N. corniger , showed low restriction (with private alleles) for E. neotenicus , and moderate restriction for A. banksi , with 20% of genetic distance explained by geographical distance between fragments. For termites, the configuration of the urban matrix contributes to functional connectivity, facilitating gene flow between forest remnants. The functional connectivity described for the three termite species in the studied urban landscape, with green patches distributed throughout the city, can be extended to other taxonomic groups, underscoring the importance of studies from this perspective for planning urban expansion strategies that ensure the conservation of green areas.

Dispersal flights of termites in an urban ecosystem in Northeastern Brazil - Rozzanna Esther Cavalcanti Reis de Chaves; Israel Soares da Silva; Alane Ayana Vieira Oliveira de Couto; Antônio Carvalho; Emanuelly Félix de Lucena; Alexandre Vasconcellos (Urban Ecosystems, 2026)
Termite alate flights represent the main means of population dispersal and may be influenced by multiple factors, such as climatic dynamics and the intrinsic structure of colonies. This study aimed to record termite flights within the urban matrix and evaluate their relationship with different levels of urbanization. Sampling was conducted over three consecutive years (2019 to 2022) at 57 locations in João Pessoa (PB), northeastern Brazil. The city contains a significant number of Atlantic Forest remnants within its urban perimeter. Termite alates were sampled during the rainy season using rooftop pools (12–48 m high), water bodies, and active searches in buildings and public squares. A total of 43 termite alate species were exclusively sampled within the urban matrix. In terms of feeding groups, 16 species were wood-feeders, 16 were soil-feeders, seven were wood–soil interface feeders, and four were wood-leaf interface feeders. Alates of all species were sampled in the most urbanized areas of the city (75% to 100% urbanization), and 83.7% of the total species were found exclusively in these areas. Furthermore, among native species, only Nasutitermes corniger is considered a pest. The other species play important ecological roles, such as decomposers or serving as food resources for other organisms, thus contributing to the maintenance of urban biodiversity.

Genetic analysis reveals urban matrix permeability to Nasutitermes corniger (Isoptera: Termitidae), a native termite species and pest in the Neotropical region - Gabriel de Sá Andrade; Rozzanna Esther Cavalcanti Reis de Figueirêdo Chaves; Alane Ayana Vieira de Oliveira Couto; Wellington Santos Fava; Alexandre Vasconcellos (Urban Ecosystems, 2026)
Urbanization is one of the main drivers of forest fragmentation and habitat loss on a global scale. This process jeopardizes biodiversity by interrupting gene flow, decreasing genetic diversity and causing local extinction. In addition, it facilitates the occurrence of synanthropic species in urban ecosystems. The Nasutitermes corniger (Blattodea: Isoptera: Termitidae) is a native neotropical termite species with a large geographical distribution in both natural and urbanized ecosystems across the Neotropical Region, and is an important pest in many South American cities. This study aimed to evaluate the genetic diversity of 30 N. corniger colonies in remnant natural forest patches inside João Pessoa’s metropolitan urban matrix region (Northeast Brazil). Thus, four individuals (soldiers) from three colonies in 10 remnant habitat patches ( N = 120) were sampled, and subsequently, all the individuals were genotyped for four microsatellite loci. No reduction in genetic diversity was found due to the absence of population genetic structure and isolation by distance. However, moderate endogamy and heterozygous deficit in most subpopulations were observed, suggesting inbreeding. It is proposed that the maintenance of N. corniger genetic diversity in urbanized ecosystems is facilitated by its generalist diet, polydomous nesting behavior (polycalism), and facultative polygyny/polyandry during the colony maturation process. Thus, the high resilience of N. corniger and its permeability within the urban matrix present significant challenges to the effective planning of control and management strategies for its infestations in the medium and long term.

Predictive empirical modeling of halogenated by-products during raw water pre-chlorination stage: Toward optimized chlorine dosing - Cristina Filomêna Pereira Rosa Paschoalato; Aline Branco de Miranda Lazari; Márcia Maísa de Freitas Afonso; Felipe Alexandre Gonçalves; Guilherme Sgobbi Zagui; Marília Vasconcellos Agnesini; Murilo Daniel de Mello Innocentini; Danilo Vitorino dos Santos; Susana Inés Segura-Muñoz (Journal of Water Process Engineering, 2026)

Criteria for choosing the best sampling method for alate termites - Amanda de Pádua; Emanuelly F. Lucena; Israel S. Silva; Alexandre Vasconcellos (International Journal of Tropical Insect Science, 2025)

New Perspectives in Stem Cell Transplantation and Associated Therapies to Treat Retinal Diseases: From Gene Editing to 3D Bioprinting - Gabrieli Bovi dos Santos; Théo Henrique de Lima-Vasconcellos; Marília Inês Móvio; Alexander Birbrair; Carolina Beltrame Del Debbio; Alexandre Hiroaki Kihara (Stem Cell Reviews and Reports, 2024)

Pest termite Cryptotermes havilandi (Sjöstedt, 1900) (Blattodea: Isoptera: Kalotermitidae) as an invasive species of natural ecosystems in northeastern Brazil - Renan Rodrigues Ferreira; Ricardo Koroiva; Flávia Maria S. Moura; Sara Rikeley Paulino Monteiro; Rozzanna Esther C. R. Figueirêdo; Matilde Vasconcelos Ernesto; Alexandre Vasconcellos (International Journal of Tropical Insect Science, 2024)

Paleosol marked by contrasting formation processes: A pilot study using digital morphometrics in Southeastern Brazil - Fernanda Almeida Bócoli; Sérgio Henrique Godinho Silva; Junior Cesar Avanzi; Bruno Montoani Silva; Vanêssa Lopes de Faria; Maria Cecília Vieira Totti; Alberto Vasconcellos Inda; Gustavo Frosi; Suane de Souza Franco Lima; Alexandre Uezu; Marco Aurélio Carbone Carneiro; Marta Vasconcelos Ottoni; et al. (CATENA, 2024)

High spatial resolution data obtained by GNSS and RPAS to assess islets flood-prone scenarios for 2100 - Rodrigo Mikosz Gonçalves; Júlia Isabel Pontes; Flávia Helena Manhães Vasconcellos; Lígia Albuquerque de Alcântara Ferreira; Heithor Alexandre de Araújo Queiroz; Paulo Henrique Gomes de Oliveira Sousa (Applied Geography, 2023)

An Evaluation of the Potential Use of Microbial Fuel Cells for Energy Production and Simultaneous Acid Mine Drainage Treatment - Luiz Henrique Zim Alexandre; Tatiana Gisset Pineda-Vásquez; Elise Sommer Watzko; Derce de Oliveira Souza Recouvreux; Regina Vasconcellos Antônio (Water, Air, & Soil Pollution, 2022)

Subterranean “oasis” in the Brazilian semiarid region: neglected sources of biodiversity - Diego de M. Bento; Marconi Souza-Silva; Alexandre Vasconcellos; Bruno C. Bellini; Xavier Prous; Rodrigo L. Ferreira (Biodiversity and Conservation, 2021)

Effect of Spatial Variation on Defensive Substances of Constrictotermes Cyphergaster Soldiers (Blattaria, Isoptera) - Antonio Paulino De Mello; Marcilio Martins De Moraes; Cláudio Augusto Gosmes Da Câmara; Alexandre Vasconcellos (Journal of Chemical Ecology, 2021)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Bushmeat consumption and its implications for wildlife conservation in the semi-arid region of Brazil - Lívia E. T. Mendonça; Alexandre Vasconcellos; Caroline M. Souto; Tacyana P. R. Oliveira; Rômulo R. N. Alves (Regional Environmental Change, 2016)